Reflective teaching in further and adult education - Hillier, Yvonne (London, United Kingdom : Continuum, 2002)
Yvonne Hillier's bestselling textbook "Reflective Teaching in Further and Adult Education" provides practical guidance for all those in the lifelong learning system who are involved with supporting the learning of young people and adults. It provides details of the changing qualifications framework, new demands for professional practice, and the ever-changing policy context. Checklists, examples and case studies have been included throughout to help the reader navigate the complex world of further and adult education, along with a glossary of unfamiliar terms. Guides to further reading and relevant websites have also been included, providing useful signposts for those looking for additional information.
Part 1. Reflective practice and policy in adult learning -- 1. Reflective practice -- 2.Policy in lifelong learning: adults and their learning -- Part 2: The practice of reflective teaching -- 3. Who are your learners? -- 4. Planning a learning program -- 5. Developing learning resources -- 6. Teaching and learning methods -- 7. Working in groups -- 8. Assessing learning -- Part 3. Evaluating and developing professional practice -- 9. Evaluation -- 10. Improving professional practice.
Includes bibliographical references and index.
Keywords: ADULT EDUCATION -- PLANNING